High temperature spherical nano-indentation of graphite crystals. (May 2022) - Marrow, T.J.; Šulak, I.; Li, B.-S.; Vukšić, M.; Williamson, M.; Armstrong, D.E.J.
Abstract: Nano-indentation at temperatures up to 600 °C has been applied to the (0001) surface of highly oriented pyrolytic graphite using a spherical diamond tip (∼10 μm diameter). Cross-sectional observations of the indentations by dark field scanning transmission electron microscopy show an increased tendency at high temperature for inelastic deformation by buckling of the graphite crystals with kink formation. Graphical abstract: Image 1